2023
DOI: 10.3390/life13030624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partial Replacement of Nitrogen Fertilizer with Organic Fertilizer on Rice Growth, Nitrogen Utilization Efficiency and Soil Properties in the Yangtze River Basin

Abstract: Cake fertilizer and dairy manure were used as experimental materials to carry out a 9-year (2012–2020) field experiment in the main rice production areas in the Yangtze River basin. Different fertilization modes were used (no fertilization, CK; chemical fertilizer application alone, HY; reduced fertilization with chemical fertilizer application, RF; cake fertilizer replacement of nitrogen fertilizer, CFR; and dairy manure replacement of nitrogen fertilizer, DMR). Changes in the total rice yield, yield componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Nonetheless, as the proportion of organic organic fertilizer nitrogen relative to synthetic fertilize nitrogen increases, both the total nitrogen accumulation in plants and grains gradually decreases, aligning with previous research findings [30][31][32][33]. Additionally, it has been observed that as the proportion of organic fertilizer replacing chemical fertilizer increases, there is a corresponding rise in organic matter content.…”
Section: Plos Onesupporting
confidence: 87%
“…Nonetheless, as the proportion of organic organic fertilizer nitrogen relative to synthetic fertilize nitrogen increases, both the total nitrogen accumulation in plants and grains gradually decreases, aligning with previous research findings [30][31][32][33]. Additionally, it has been observed that as the proportion of organic fertilizer replacing chemical fertilizer increases, there is a corresponding rise in organic matter content.…”
Section: Plos Onesupporting
confidence: 87%
“…For instance, research by [38] demonstrated that the combined application of urea (chemical fertilizer) and poultry manure (organic fertilizer) in equal proportions resulted in higher plant height, increased tiller production, and improved grain yield in rice. Another study by [39] supported these findings, revealing that the 50:50 ratio of chemical and organic nitrogen fertilizers improved nutrient uptake efficiency, enhanced photosynthesis, and ultimately led to higher rice yields. These findings underscore the importance of integrating chemical and organic nitrogen sources in a balanced ratio to maximize the growth and yield potential of rice crops.…”
Section: Discussionmentioning
confidence: 81%
“…At present, an effective way to improve soil fertility and nutrient vitality is by increasing the application of organic fertilizers, purifying the soil environment and ensuring high yield and quality of crops based on various amino acids and humus [1][2][3]. Previous studies showed that organic fertilizers contain a large number of amino acids and organic matter, as well as nitrogen, phosphorus, potassium and other nutrients required for plant growth [4]. Also, they optimize the rhizosphere bacterial community structure and improve soil fertility and soil continuous production capacity [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that organic fertilizers contain a large number of amino acids and organic matter, as well as nitrogen, phosphorus, potassium and other nutrients required for plant growth [4]. Also, they optimize the rhizosphere bacterial community structure and improve soil fertility and soil continuous production capacity [4]. Gelaye and Tadele (2022) suggested a combination of two cabbage buds and five tons of farmyard manure/ha −1 fertilizer for the economical production of cabbage [5].…”
Section: Introductionmentioning
confidence: 99%